The expressionist debate in the light of the concerns of postmodernity : Lukacs, Brecht, Lyotard and Habermas - Fischer, Bettina (Department of English Language and Literature, 2016)
This dissertation investigates the debate between Georg Lukács and Bertolt Brecht in the 1930s, known as the Expressionist Debate and the controversy between Jean-Francais Lyotard and Juergen Habermas. which took place in the 1980s. The two debates. both of which took place among writers of the Left are juxtaposed in order to shed more light on the issues at stake in the Expressionist Debate when looked at in the light of postmodern concerns. The dissertation is based on selected texts by each of the four writers. Bibliography: pages 82-85.